Advocacy Disabled in Publishing Newspapers Media in Malaysia - Hazzlan Sama (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2017)
This article discusses the role of news media in communicating information about Disabled news to the public. The focus of the discussion centered issue and advocacy role of the news media conducted to understand the issues of persons with disabilities. Studies conducted using the method of analysis to systematically review the library of selected journals that conduct media exposure of persons with disabilities at the global level and so focused towards media conference in Malaysia. In this research, the data was obtained through databases ERIC, google scholar, Journal of Education, Journal of Social Sciences and Journal of Communication. A total of 30 articles were based on keywords such as disabled people, newspapers, news exposure to people with disabilities. However, researchers have obtained 13 articles that met after being filtered. The results obtained showed that the press releases are also still not open and not to report the news on disabilities. This is because there is a stigma that prevents acceptance of disabilities such as discrimination and negative attitudes towards them. Outlook negative stereotypes of people with disabilities who are strangers, the great ones, defects often appear in the media. Even now there is increasing advocacy for press media publishing news on this special group but the content or dissemination of information about them is still less show.